State of wonder ebook - Patchett, Ann (2011)
"A nail-biting narrative, setting stark human dilemmas against a lush, exotic backdrop."— People "Extraordinary. . . . Nothing is as it seems, and the ending is as shocking as it's satisfying." — Boston Globe From award-winning, New York Times bestselling author Ann Patchett, a provocative and assured novel of morality and miracles, science and sacrifice set in the Amazon rainforest In a narrative replete with poison arrows, devouring snakes, scientific miracles, and spiritual transformations, State of Wonder presents a world of stunning surprise and danger, rich in emotional resonance and moral complexity. As Dr. Marina Singh embarks upon an uncertain odyssey into the insect-infested Amazon, she's forced to surrender herself to the lush but forbidding world that awaits within the jungle. Charged with finding her former mentor Dr. Annick Swenson, a researcher who has disappeared while working on a valuable new drug, she will have to confront her own memories of tragedy and sacrifice as she journeys into the unforgiving heart of darkness. Stirring and luminous, State of Wonder is a world unto itself, where unlikely beauty stands beside unimaginable loss beneath the rain forest's jeweled canopy. Patchett delivers a gripping adventure story and a profound look at the difficult choices we make in the name of discovery and love.